Efficient nitrate removal of immobilized mixed aerobic denitrifying bacteria and community dynamics response to temperature and low carbon/nitrogen polluted water. (October 2022) - Chen, Zhaoying; Zhang, Tianna; Meng, Jiajing; Zhou, Shilei; Zhang, Ziwei; Chen, Zhe; Liu, Yilin; Zhang, Jiafeng; Cui, Jiansheng
Graphical abstract: Highlights: NO3 – -N removal efficiencies ranged from 89.71% to 98.25% at low C/N. CIMABD had a relatively higher richness, diversity, and evenness. Magnetospirillum were the dominant genera based on nap A gene sequencing. IMADB reduced the NO3 – -N of source water from 2.34–2.37 mg/L to 0.77–0.87 mg/L. Abstract: The denitrification performance of immobilized mixed aerobic denitrifying bacteria (IMADB) was investigated. IMADB displayed strong temperature adaptability under low Carbon/Nitrogen conditions. At 5, 15, and 25 °C, the nitrate removal efficiencies of volcanic rock and polyester fiber sponge immobilized system reached 83.95%-98.25% and 89.71%-98.14%, respectively. The nitrate content removed by the carrier accounted for 41.18%-82.47% of the nitrate content removed by the immobilized system at different temperature, and played a major role in nitrate removal. The lower the temperature, the greater the role of the carrier. At the same temperature, carrier had a relatively higher richness, diversity, and evenness. Network analysis revealed that carrier species, which were positively correlated with nitrate removal efficiency, had the largest OTUs and abundance. Meanwhile, carrier had the widest niche. The total nitrogen removal efficiency of IMADB reached 56.10%-62.31% in the natural water system, highlighting a promising application prospect.